2023
DOI: 10.7759/cureus.45979
|View full text |Cite
|
Sign up to set email alerts
|

Kikuchi Fujimoto Lymphadenitis: A Rare Association With COVID-19 Vaccination

Priya R Nair,
Nandkishor J Bankar,
Amruta Choudhary
et al.

Abstract: Kikuchi-Fujimoto disease (KFD), also known as histiocytic necrotizing lymphadenitis, is an uncommon cause of protracted cervical lymphadenopathy in both children and adults. Although the majority of cases have been documented in Asia, this disease has been characterized globally since it was first identified in Japan in 1972. KFD's etiology is not entirely understood, although various theories have been postulated. Usually benign, Kikuchi-Fujimoto disease resolves within six months. KFD must be distinguished f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…A literature search was conducted on PubMed and google scholar with keywords including Kikuchi, Fujimoto, COVID‐19, and SARS‐CoV‐2. Since the start of the pandemic, 13 cases of post‐COVID‐19 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 KFD and 12 cases of post‐COVID‐19 vaccination 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 KFD have been reported worldwide. It has been suggested that SARS‐CoV‐2 can excessively stimulate the immune system, leading to generation of autoimmunity, 33 but the exact pathophysiological mechanism of post‐COVID‐19 KFD is still unknown.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A literature search was conducted on PubMed and google scholar with keywords including Kikuchi, Fujimoto, COVID‐19, and SARS‐CoV‐2. Since the start of the pandemic, 13 cases of post‐COVID‐19 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 KFD and 12 cases of post‐COVID‐19 vaccination 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 KFD have been reported worldwide. It has been suggested that SARS‐CoV‐2 can excessively stimulate the immune system, leading to generation of autoimmunity, 33 but the exact pathophysiological mechanism of post‐COVID‐19 KFD is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…4 COVID-19, the disease caused by SARS-CoV-2 infection, was suggested to trigger KFD. 5 Cases of post-COVID-19 [5][6][7][8][9][10][11][12][13][14][15][16][17] KFD and post-COVID-19 vaccine [18][19][20][21][22][23][24][25][26][27][28][29][30] KFD have emerged in recent years. In this article, we report the first case of post-COVID-19 KFD in Hong Kong.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation